Next steps: towards child-focussed nursing - Randall, D.; Munns, Ailsa; Shields, L. (Cambridge Publishing, 2013)
Family-centred care (FCC) is widely promoted as a model for children’s health care in many countries throughout the world and in all spheres of children’s nursing education, management, policy and practice. However, research has failed to show that clinical practice uses the partnership model, central to FCC. In this paper we suggest that, in part, the failure of FCC, as a project, is due to the lack of attention paid to the cultural, social and political context in which children’s health care is delivered. We propose that while the concepts of cultural safety and ethical symmetry may not replace that of FCC, they can be used to locate child-centred care within the complexity of children’s lives, as lived with illness.